Solar photovoltaic based air cooling system for vehicles. (January 2019) - Pang, Wei; Yu, Hongwen; Zhang, Yongzhe; Yan, Hui
Abstract: The conventional automotive air conditioning system was driven by internal combustion engine or power battery, which increased the oil consumption and vehicle carbon emission. In this study, a direct current (DC) air conditioning system powered by solar photovoltaic module (PV) has been designed to solve the problem of temperature increasing inside the vehicle when stops in the broiling summer. The purpose of this work is to design a whole DC air conditioning system with R134a as refrigerant, replacing the power source with solar energy. The result shows that the environmental condition in the vehicle has obviously improved by the DC air conditioning system, meeting the requirements of human bodies. In addition, in the experiment, the minimum refrigerating capacity should be ∼1500 W, maintaining the thermal equilibrium inside the vehicle under the sun blazing, when the vehicle stops and no person inside. The work will prompt further research of solar energy and development of solar electric vehicle air conditioning system. Highlights: A solar powered air condition system of vehicle was examined for PV panels and batteries. The result shows that the DC air conditioning system in the vehicle could be meet the requirements of human bodies. The minimum refrigerating capacity should be ～1500 W in the experimental condition. The control strategy was studied for the DC air conditioning system.